Rieske non-heme iron-dependent oxygenases catalyse diverse reactions in natural product biosynthesis. Issue 7 (13th April 2018) - Perry, Christopher; de los Santos, Emmanuel L. C.; Alkhalaf, Lona M.; Challis, Gregory L.
Abstract : The role played by Rieske non-heme iron-dependent oxygenases in natural product biosyntheses is reviewed, with particular focus on experimentally characterised examples. Abstract : Covering: up to the end of 2017 The roles played by Rieske non-heme iron-dependent oxygenases in natural product biosynthesis are reviewed, with particular focus on experimentally characterised examples. Enzymes belonging to this class are known to catalyse a range of transformations, including oxidative carbocyclisation, N -oxygenation, C -hydroxylation and C–C desaturation. Examples of such enzymes that have yet to be experimentally investigated are also briefly described and their likely functions are discussed.